Comparative Study of Organizational Communication Theories Perspectives (Classical, Humanistic, Integration, and Contemporary Perspectives) - Fitri Meliya Sari; Yusnadi Yusnadi; Hasrat Efendi Samosir (State Islamic Institute of Bone, Indonesia, 2023)
Organizational communication is used to achieve common goals in an organization. Organizational communication is the transmission of information so as to form information flows that give rise to information networks. In understanding communication in an organization there are several perspectives that can be used, namely: Classical, Humanistic, Integration and Contemporary. Perspective is a point of view in interpreting a problem. In this study, researchers discuss comparative studies from the perspectives of organizational communication theory. Where researchers compare the advantages and weaknesses of each perspective with qualitative approaches and comparative methods. In comparative studies, each of the above perspectives has different advantages and disadvantages, and is selected according to the needs of the organization and the specific situation. However, in general, the four perspectives can be used as a guide to understanding how communication can be used to achieve organizational goals. It is important to understand that each perspective has its own advantages and disadvantages, so there is no one theory that can be used to solve all problems in organizations. Although the four perspectives of organizational communication theory have different focuses and goals, they are interrelated and can contribute to a more holistic understanding of communication in organizations.